Viewpoint of physicians and pharmacists on electronic prescription service: Short Communication - Maryam Barazandeh; Azam Salehzadeh; Malihe Ram; Ahmad Negahban; Arash Shirdel; Razieh Farrahi (مجله دانشگاه علوم پزشکی بیرجند)
Electronic prescription services can enhance patient safety and the quality of healthcare services by reducing medical mistakes. Therefore, this study aimed to examine the perspectives of physicians and pharmacists in Birjand regarding electronic prescriptions. This descriptive-applied study was conducted cross-sectionally during 2023-2024 in public and private hospitals, clinics (including charity, private, government-affiliated, and social security), as well as medical offices and pharmacies in Birjand County. Based on a standard deviation of 0.9, an acceptable margin of error of 0.2, and a 20% anticipated dropout rate, a sample size of 100 physicians and pharmacists was determined and recruited using convenience sampling. Data were collected using a two-part questionnaire. The first part included demographic information, such as gender, age, occupation, workplace, work experience, and electronic prescription experience. The second part consisted of 31 specific items across nine fields. The researcher personally distributed the questionnaire to the participants. The collected data were then analyzed using descriptive-analytical tests in SPSS software version 22. The average scores in the evaluated fields, from highest to lowest according to users' perspectives, were as follows: social influence (4.01), actual use (3.71), habit (3.66), intention to use (3.39), trust (3.15), expected performance (3.07), expected effort (2.78), price value (2.73), and facilitating conditions (2.32). A significant inverse correlation was observed between age and factors such as expected effort (r=-0.615), expected performance (r=-0.44), trust (r=-0.305), price value (r=-0.397), and facilitating conditions (r=-0.584) (P<0.05). Female pharmacists and physicians generally held more favorable views across most dimensions, except for social influences. Notably, expected effort and performance differed significantly between male and female participants (P<0.05). In conclusion, physicians and pharmacists held a moderate perspective on the use of electronic prescription services.